Aile fotoğrafı - Ok, Sebla Selin (My University, 2007)
Fotoğraflar değişebilirliğin sembolüdürler. Zamanın akışına tanıklık ederken, bitmez tükenmez bir olumlama arayışını temsil ederler. Bu nedenle fotoğrafın ruhu doyumsuz bir serüvencinin ruhuna benzer. Her serüveninde yeni bir keşif vardır fakat keşfettiği şeyler görülmeyeni ortaya çıkarmak değil tam tersine zaten orada olanı her seferinde başka önermelerle görünür kılmaktır. Fotoğrafların olaylar, nesneler, kavramlar üzerindeki algısı tümden gelen bir armoniyle oluşmaz, fotoğraflar ayrıntıların ironik izdüşümüdürler. İnsan, yaşamını ayrıntılar üzerinden kurgulayarak biçimlendiren bir varlıktır. Bu nedenle de insan göstergeler imparatorluğunun öznesi konumundadır. Böylece insanın fotoğraf çekme ve fotoğrafının çekilmesi isteği ve heyecanı anlaşılabilir. Fakat burada bahsedilen heyecan ve istek fotoğrafın teknik donanımıyla bir sanat eseri yaratmaktan çok kendimiz için fotoğraf çekmek ve fotoğraf çektirmek eylemleridir. Bu açıdan bakıldığında anı fotoğrafları ve aile fotoğrafları en belirgin örnekleri oluştururlar. Kendimizi, benliğimizi, köklerimizi, yaşamdaki yerimizi betimleyen bu fotoğraflar yaşamdaki en büyük zaafımızı yani yaşama bağlılığımızı gözler önüne serer. Yalnızca kendi var oluşumuzu meşru kılmak adına fotoğraflamak ve fotoğraflanmak amatör bir çaba olarak nitelendirilemez. Bu bir özgürlük manifestosudur. Bu çalışmanın araştırma konusu aile fotoğrafları, amacı ise aile fotoğrafları üzerinden insanın yaşamı biriktirerek oluşturan, sosyal bir varlık oluşuna dikkat çekmektir. Birinci bölümde insanın gerçek görüntüye karşı gösterdiği ilgi ve fotoğrafın icadıyla birlikte gelişen yeni algı sistemini incelenmiştir. İkinci bölümde aile, toplum ve fotoğraf kavramları birbirleriyle ilişkilendirilerek ele alınmış, etnik kültürleri fotoğraflama çabası ve yöntemleri örneklerle tartışılmıştır. Üçüncü bölümde fotoğrafın bulunduğu tarihten itibaren insanın zaman içerisindeki devinimi onar yıllık periyotlar şeklinde aile fotoğrafları üzerinden yorumlanmıştır. Dördüncü ve son bölümde ise aile fotoğraflarını konu alan farklı kavramsal yaklaşımlardan örnekler sunulmuştur.

Photographs are symbols of changeability. While they witness the passage of time, they at the same time symbolize an endless search of affirmation. It is therefore true that the soul of the photograph is similar to the soul of an insatiate adventurer. There is a new discovery in every adventure, but those photograph discovers are not to expose the unseen, but, on the contrary, to make visible that which already exists under different hypotheses, every single time. The perception of the photographs vis-à-vis events, objects and concepts is not composed of a deductive harmony; photographs are ironic projections of the details. The human being is an existence who shapes his/ her life by assembling it through the details. The human being therefore assumes the role of being the subject of the empire of the signs. In this way, the desire and the enthusiasm of the human being vis-à-vis taking photographs and his photographs being taken, in turn, can be well understood. The desire and enthusiasm, here, is not to create an art piece using technical equipment, but rather to take photographs and have our photographs taken for our own pleasure. From this perspective, recollection photographs and family photographs constitute the most distinct examples. These photographs which depict our selves, our ego, our roots, our position in life, display our most acute weakness, that is, our close attachment to life. To photograph and be photographed only to legitimize our own existence, can not be featured as an amateur effort. This is a manifesto of freedom. The topic of this research is family photographs, and its objective is to draw attention to the human being’s composing life by accumulating it via the family photographs, thereby becoming a social being. In the first part, the concern of the human being towards the real image and the new perception system developed by the advent of the photograph are examined. In the second part, family, society and photograph concepts are discussed by associating them to one another, and the effort and methods to photograph ethnic cultures are debated through examples. In the third part, the movement of the human being through time is interpreted, starting from the date the photograph was discovered, as periods of ten years based on the family photographs. In the fourth and the last part, examples are provided on the differing conceptual approaches which take the family photographs as their subject matter.
Keywords: Fotoğrafçılık_Aile